The current status of reversal therapy in Japan for elderly patients with head injury treated with antithrombotic agents: A prospective multicenter observational study - Eiichi Suehiro; Naoto Shiomi; Hiroshi Yatsushige; Shin Hirota; Shu Hasegawa; Hiroshi Karibe; Akihiro Miyata; Kenya Kawakita; Kohei Haji; Hideo Aihara; Shoji Yokobori; Motoki Inaji; et al. (Heliyon, 2024)
Background: Acute exacerbation of head injury in elderly patients due to use of antithrombotic agents has become a concern in countries with aging populations. Reversal agents are recommended for treatment, but its usage is unclear. Therefore, we conducted a prospective observational study in this patient population to monitor usage of reversal therapy. Methods: The subjects were 721 elderly patients aged ≥65 years old who were hospitalized in 15 centers from December 2019 to May 2021. Patients were divided into groups who did not receive antithrombotic agents (Group A), who received antithrombotic agents, but did not receive reversal therapy (Group B), and were treated with antithrombotic agents and reversal therapy (Group C). Age, gender, mechanism of injury, neurologic and imaging findings on admission, clinical course after admission and surgery, outcomes and complications were compared among these groups. Time from injury to reversal therapy was examined based on outcomes to investigate trends in the timing of administration of the reversal agent. Results: Acute exacerbation during the clinical course occurred in 9.8 %, 15.8 % and 31.0 % of cases in Groups A, B and C, respectively, and differed significantly among the groups. On head CT, the incidences of hematoma were 35.7 %, 36.5 % and 60.4 %, respectively, with this incidence being significantly higher in Group C; and the respective rates of craniotomy were 18.8 %, 14.0 % and 50.9 %, again with this rate being significantly higher in Group C. The good outcome and mortality rates were 57.1 %, 52.5 % and 35.8 %, and 14.5 %, 18.0 % and 24.5 %, respectively, and both were poorest in Group C. Times from injury to treatment with a reversal agent were significantly shorter in patients without compared to those with acute exacerbation (405.9 vs. 880.8 min) and in patients with favorable outcomes compared to those with unfavorable outcomes (261.9 vs. 543.4 min). Conclusion: Similarly to previous studies, the incidence of acute exacerbation was increased by use of antithrombotic agents. These results suggest that patients in Japan who require hematoma evacuation due to symptom exacerbation tend to be treated with reversal agents. Although it is difficult to assess the efficacy of reversal therapy from this study, earlier treatment with reversal agents before the occurrence of acute exacerbation may be useful to improve outcomes.